PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS X DI MAN 2 PONTIANAK - Siregar, Mohammad Ridho Alamsyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to (1) analyse the needs of Augmented Reality (AR) learning media development (2) produce learning media products (3) assess the feasibility of learning media (4) determine the increase in student learning motivation. This research uses the Design Based Research (DBR) development model. The results showed that (1) teachers and students need technology-based learning media in accordance with the times. (2) The product design produced in this study is in the form of Augmented Reality (AR) based learning media for market material in the economy. (3) The validation assessment conducted by media experts, material experts, teacher assessment and learner assessment shows that Augmented Reality (AR) based learning media is categorised as feasible. (4) The increase in students' learning motivation towards the use of Augmented Reality (AR) based learning media has increased by 4% from 79% with a medium category to 83% with a high category.